Kompetencja sądu administracyjnego do uznania w wyroku uprawnienia lub obowiązku wynikających z przepisów prawa - Ciesielska, Agnieszka (Studia Prawa Publicznego, 2019)
The purpose of the article is to present the competence of the administrative court indicated in Article 146 § 2 of the Act of 30 August 2002 – the Law on proceedings before administrative courts (LPAC). In accordance with this provision, in matters concerning complaints against an Act or an action related to public administration referred to in Article 3 § 2 point 4 of the LPAC, the court may recognize in its judgment a right or an obligation arising from the provisions of law and may issue a relevant decision in the matter if it first annuls the act or declares that the action is with no legal effect pursuant to Article 146 § 1 of the LPAC. It must be emphasized however, that Article 146 § 2 of the LPAC is not an independent basis for issuing a judgment and the doctrine often presents differing views. It should be assumed that the court may recognize the right or the obligation of an individual that arises from the provisions of law if the nature of the case permits doing so and when the facts and the legal framework of the case do not raise reasonable doubts. Unfortunately, judicial case studies show that this possibility is rarely used. Furthermore, courts encounter numerous problems in applying Article 146 § 2 of the LPAC, most probably because of the huge controversy regarding this procedural institution. Firstly, there is no consensus as to the function of the judicial decision based on the provision in question, and the interpretation of its facultative nature is also problematic. In the author’s opinion administrative courts should use the competence referred to in Article 146 § 2 of the LPAC more frequently. Such a change of practice would increase the effectiveness of judicial review of public administration as well as will enhance the level of protection of individual rights. The article also contains some interesting examples of the application of Article 146 § 2 of the LPAC.